UJI LOPAT BAKTERI PATOGEN DARI BEBERAPA TANAMAN - Asrul, Asrul (FAPETKAN UNTAD, 2005)
Several bacteria isolates obtained from paddy rice plants, banana plants, potato tubers, carrot tubers and soybean seeds were grown on NA, CPG and King’s B media for examination of their physiological characteristics using LOPAT test. The tests lead to the indication that each isolate was the species of bacteria that was known to cause disease on the corresponding plants. Hypersensitivity tests, however, showed that only banana and potato isolates were pathogenic on tobacco plants.Key words : LOPAT, bacteria, plant, hypersensitive.